The environmental impacts of industrial effluents: The case of the Frigorífico São Francisco in Redenção-PA (Research, Society and Development, 2023)
The environmental impacts of refrigeration and slaughterhouse activities are related to the high consumption of water, which generates effluents with great polluting potential from the stages of the production process. To minimize the use of water and reduce the impacts caused by the activity of production of aquatic organisms, many technological systems are emerging for the reuse of effluents, however, many slaughterhouses use treatment through stabilization ponds composed of multiple treatment processes, it is the Frigorifico São Francisco, located in the city of Redenção-PA. Therefore, the research based its study on the treatment of effluents from the aforementioned refrigerator, pointing out the forms of effluent treatment provided for by the Establishment Self-Control Program (PAC), and also observed the relevant legislation such as RIISPOA, Ordinance nº 365/2017 of the MAPA, CONAMA and other legislation dealing with the regulation for refrigerators. For a better understanding, it was necessary to bring the definitions and stages of slaughter, because in this way it is possible to understand the amount of residues with a high level of putrefaction produced by the slaughter and the level of pollution and contamination that such residues can bring to the environment. According to the results, it was possible to prepare the impressions in the form of a technical report, which will be part of this scientific production.